ACADEMIC WORDS IN ABSTRACT OF UNDERGRADUATE THESIS - Dewintha, Rezza; Sudarsono, Sudarsono; Ikhsanuddin, Ikhsanuddin (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractCorpus linguistics is the study of language data on a large scale, computerization data analysis of extensive collections of written texts. This study is a academic words in abstract of undergraduate thesis of English Language Education Study Program, Teacher Training Facutly, Tanjungpura University, submitted in year 2012-2016, using AntConc Program. There are six (6) research questions raise in this study; (1) the categories of POS tagset; (2) the most dominant POS tagset; (3) The most dominant academic word; (4) the role of AWL in students’ abstract; (5) the most dominant AWL sublist; and (6) the comparison between AWL and non-AWL. The findings are; (1) there are 31 types of Tree Tagger tagset and Brown Corpus Tagset; 11710 tokens (18,2%) for Noun, 8198 tokens (12,8%) for Determiners, 5289 tokens (8,2%) for Preposition, 4075 tokens (7,3%) for Verb, 2410 tokens (3,7%) for Adjective, 809 tokens (1,3%) for Conjunction, 527 tokens (0,85%) for adverb, 2 tokens (0,003%) for Interjection; (2) NN as the most frequent tagset, (3) the most frequent academic word is Research, (4) only 0,00522% or 183 types of academic words used by undergraduate students, (5) sublist 1 as the most frequent sublist used, and (6) there are 1974 non-academic words used. There are 208 corpora which are gathered from UP4I since 2012-2016.This research is useful for English Language teacher in examine their students’ writing easily, especially focus on concordance entirely and lexical study. It leads to more principled classroom materials and activities and lead students to have best understanding on language analysis.Keywords: Corpus linguistics, Lexical study, AWL